Ocorrência sorológica de Babesia bovis, Babesia bigemina e Anaplasma marginale em bovinos e bubalinos no estado do Pará, Brasil - Silva, Jenevaldo Barbosa da [UNESP]; Cordeiro, Matheus Dias; Santana Castro, Gustavo Nunes de; Santos, Priscilla Nunes dos; Fonseca, Adivaldo Henrique da; Reis, Alessandra Belo; Silva e Silva, Natália; Barbosa, José Diomedes (Univ Estadual Londrina, 2014)
Among the major diseases that affect cattle and water buffaloes, the tick-borne diseases are detaches. Bovine babesiosis caused by Babesia bigemina and Babesia bovis, and anaplasmosis, caused by Anaplasma marginale rickettsia, are of great economic importance to cattle diseases. The aim of this study was to compare the serologic occurrence for the agents of tick fever in cattle and water buffaloes in the middle region southeast of the state of Para, northern Brazil. Blood samples were collected from 679 beef cattle (Nelore) and 430 water buffaloes (Mediterranean and Murrah) in eight cities of middle region southeast of Para, Brazil. The research of antibodies IgG against A. marginale, B. bigemina and B. bovis was performed through of the indirect enzyme-linked immunosorbent assay (iELISA). Cattle compared to buffaloes showed higher occurrence of antibodies against B. bovis (97,34% and 33.95%), B. bigemina (97,34% and 27.21%) and A. marginale (74,52% and 47.90%), respectively. The probability of cattle are serologically positive to A. marginale, B. bovis and B. bigemina was 1,5 (74,52/47,90%), 3,58 (97,34/27,21%) and 2,87 (97,34/33,95%) times higher than that buffaloes, respectively. These results suggest that buffaloes may be more resistant to vectors being subjected to a lower rate of infection than cattle.

Dentre as principais enfermidades que acometem bovinos e bubalinos, destacam-se as doenças transmitidas por carrapatos. As babesioses bovinas, causadas por Babesia bigemina e Babesia bovis, e a anaplasmose, causada pela rickettsia Anaplasma marginale, são doenças de grande importância econômica para a bovinocultura. O objetivo deste trabalho foi comparar a ocorrência sorológica para os agentes da Tristeza Parasitária em bovinos e bubalinos na mesorregião sudeste do estado do Pará, região norte do Brasil. Foram efetuadas coletas de sangue de 679 bovinos de corte (Nelore) e 430 bubalinos (Mediterrâneo e Murrah) em oito cidades da mesorregião do sudeste do estado do Pará, Brasil. A pesquisa de anticorpos da classe IgG contra A. marginale, B. bigemina e B. bovis foi realizada por Ensaio de Imunoadsorção Enzimático Indireto (iELISA). Bovinos, quando comparados a bubalinos, apresentaram maior ocorrência de anticorpos contra B. bovis (97,34% e 33.95%), B. bigemina (97,34% e 27.21%) e A. marginale (74,52% e 47.90%), respectivamente. O número de bovinos soropositivos para A. marginale, B. bovis e B. bigemina foi 1,5 (74,52/47,90%), 3,58 (97,34/27,21%) e 2,87 (97,34/33,95%) vezes maior do que os bubalinos, respectivamente. Os resultados permitem concluir que, habitando a mesma mesorregião e sendo submetidos a mesma pressão de vetores e agentes, os bubalinos apresentaram ocorrência de anticorpos contra os agentes da TPB inferior aos bovinos. Esses resultados sugerem que os búfalos podem ser mais resistentes aos vetores sendo submetidos a uma menor taxa de infecção que os bovinos.
Serological occurrence of Babesia bovis, Babesia bigemina and Anaplasma marginale in cattle and water buffaloes of Para, Brazil
Keywords: Anaplasmosis; Babesiosis; Nelore bovine; Water buffaloes; Anaplasmose; Babesiose; Bovinos nelore; Búfalo d’agua